Intrapancreatic Accessory Spleen Detected by 68Ga DOTANOC PET/CT and 99mTc-Colloid SPECT/CT Scintigraphy. (May 2015) - Collarino, Angela; del Ciello, Annemilia; Perotti, Germano; Rufini, Vittoria
<x xml:space="preserve">Abstract</x> Abstract A 77-year-old man was referred to our center for a suspected neuroendocrine neoplasm in the pancreatic tail, incidentally detected at CT. 68Ga DOTANOC PET/CT showed intense tracer uptake in the pancreatic lesion. At MRI, the lesion was similar to the spleen on all sequences, suggesting the presence of intrapancreatic accessory spleen. A 99mTc-colloid SPECT/CT scan performed to differentiate spleen tissue from neuroendocrine tumor revealed a focal uptake in the pancreatic lesion, thus confirming the presence of ectopic spleen and avoiding unnecessary surgery.